Expanding the reach of evidence-based mental health interventions to private practice: Qualitative assessment using a policy ecology framework - Frank, Hannah E.; Milgram, Lauren; Freeman, Jennifer B.; Benito, Kristen G. (Frontiers in Health Services, 2022)
Background: Evidence-based interventions (EBIs) for mental health disorders are underutilized in routine clinical practice. Exposure therapy for anxiety disorders is one particularly difficult-to-implement EBI that has robust empirical support. Previous research has examined EBI implementation determinants in publicly funded mental health settings, but few studies have examined EBI implementation determinants in private practice settings. Private practice clinicians likely face unique barriers to implementation, including setting-specific contextual barriers to EBI use. The policy ecology framework considers broad systemic determinants, including organizational, regulatory, social, and political contexts, which are likely relevant to EBI implementation in private practice settings but have not been examined in prior research. Methods: Qualitative interviews were conducted to assess private practice clinicians’ perceptions of EBI implementation determinants using the policy ecology framework. Clinicians were asked about implementing mental health EBIs broadly and exposure therapy specifically. Mixed methods analyses compared responses from clinicians working in solo versus group private practice and clinicians who reported high versus low organizational support for exposure therapy. Results: Responses highlight several barriers and facilitators to EBI implementation in private practice. Examples include determinants related to organizational support (e.g., colleagues using EBIs), payer restrictions (e.g., lack of reimbursement for longer sessions), fiscal incentives (e.g., payment for attending training), and consumer demand for EBIs. There were notable differences in barriers faced by clinicians who work in group private practices compared to those working in solo practices. Solo private practice clinicians described ways in which their practice setting limits their degree of colleague support (e.g., for consultation or exposure therapy planning), while also allowing for flexibility (e.g., in their schedules and practice location) that may not be available to clinicians in group practice. Conclusions: Using the policy ecology framework provides a broad understanding of contextual factors that impact private practice clinicians’ use of EBIs, including exposure therapy. Findings point to potential implementation strategies that may address barriers that are unique to clinicians working in private practice.